Phase transformation mechanism of In-Sb-Te through the boundary reaction between InSb and InTe - Kim, Yong Tae; Kim, Eun Tae; Kim, Chung Soo; Lee, Jeong Yong (WILEY-V C H VERLAG GMBH, 2011)
The boundary reaction between InSb and InTe bilayers shows that In3Sb1Te2 (IST) is formed at the InTe side first due to the diffusion of Sb atoms from InSb to InTe rather than the diffusion of Te atoms from InTe to InSb at the crystallization temperature of IST. The diffusion of Sb atoms into InTe changes the atomic configuration of InTe, which leads to small lattice distortion and a coherent boundary region for the formation of IST crystalline thin films. (C) 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: CHANGE MEMORY; MULTIBIT STORAGE; FILM